Strengthening teachers in realizing child-friendly schools for positive character development - Susanto Susanto (Faculty of Engineering, Universitas Sultan Ageng Tirtayasa, 2022)
This article contains the results of community service carried out by postgraduate lecturers at the PTIQ Jakarta Institute. The implementation of the activity was motivated by the common understanding of teachers on child-friendly school programs in developing students' character, which became a national issue. Implementing the service is expected to improve the competence of teachers in Tanggamus Regency, Lampung Province, especially in realizing child-friendly schools. The implementation method used is training with demonstration. The use of the method is considered following the target and assisted object. The training participants consisted of teachers in Tanggamus Regency, Lampung Province, totaling 75 people, and it was held on Wednesday, September 15, 2021. The implementation of this activity showed that teachers in Tanggamus Regency did not comprehensively understand child-friendly schools in students' character development. After the activity, it was found that all teachers understood conceptually child-friendly schools, and teachers understood the urgency of realizing child-friendly schools. This program has the potential to develop the character of Indonesian children. Artikel ini memuat tentang hasil pengabdian masyarakat yang dilakukan oleh dosen pascasarjana Institut PTIQ Jakarta. Pelaksanaan kegiatan ini dilatarbelakangi rendahnya pemahaman guru terhadap program sekolah ramah anak dalam pengembangan karakter peserta didik yang menjadi isu nasional. Terlaksananya pengabdian ini diharapkan dapat meningkatkan kompetensi guru di Kabupaten Tanggamus Provinsi Lampung khususnya dalam mewujudkan sekolah ramah anak. Metode pelaksanaan yang digunakan adalah pelatihan dengan demonstrasi. Penggunaan metode ini dianggap sesuai dengan target dan objek dampingan. Peserta pelatihan ini terdiri dari guru-guru di Kabupaten Tanggamus Provinsi Lampung berjumlah 75 orang, dan dilaksanakan pada hari Rabu, 15 September 2021. Hasil pelaksanaan kegiatan ini menunjukkan bahwa guru-guru di Kabupaten Tanggamus belum memahami secara komprehensif tentang sekolah ramah anak dalam pengembangan karakter peserta didik. Setelah kegiatan, diketahui bahwa semua guru telah memahami secara baik tentang sekolah ramah anak secara konseptual, serta guru memahami tentang urgensi mewujudkan sekolah ramah anak. Program ini berpotensi mengembangkan karakter anak-anak Indonesia.